Productivity Growth and Value Chains in Four European Countries - Karpowicz, Izabela (IMF Working Papers; Working Paper ;, 2020)
Advanced economies have been witnessing a pronounced slowdown of productivity growth since the global financial crisis that is accompanied in recent years by a withdrawal from trade integration processes. We study the determinants of productivity slowdown over the past two decades in four closely integrated European countries, Austria, Denmark, Germany and the Netherlands, based on firm-level data. Participation in global value chains appears to have affected productivity positively, including through its effect on TFP when facilitated by higher investment in intangible assets, a proxy for firm innovation. Other contributors to productivity growth in firms are workforce aging, access to finance, and skills mismatches.